2009
DOI: 10.1016/j.tox.2009.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of developmental exposure to di-n-butyl-phthalate (DBP) on rat prostate: Proliferative and inflammatory disorders and a possible role of androgens

Abstract: In the present study we evaluated the toxic effects on the male adult rat prostate of DBP exposure during fetal and lactational periods, because although many studies have addressed the influence of phthalates on the male reproductive system, only a few have discussed their possible effects on prostate development. Pregnant females were distributed into two experimental groups: Control (C) and Treated (T). The females of the T group received DBP (100mg/kg, by gavage) from gestation day 12 to postnatal day 21, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 51 publications
3
42
1
3
Order By: Relevance
“…This result is in agreement with other rodent studies which indicates that prenatal or neonatal exposure of male rat and mice to low doses of estradiol and other estrogenic chemicals like BPA and offspring can lead to androgen sensitivity and consequently to an increased expression of AR in the prostate in pubertal and young adults rodents (Nagel et al, 1997;Gupta, 2000;Brandt et al, 2014). Furthermore, in a previous study we observed that estrogen supplementation even in a lowandrogen environment (after castration) increased AR expression in Mongolian gerbil ventral prostate through paracrine signaling mechanisms involving ER-a (Scarano et al, 2009). Maternal dietary GEN tended to normalize AR expression in the VL in male offspring from dams exposure to low-dose BPA.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This result is in agreement with other rodent studies which indicates that prenatal or neonatal exposure of male rat and mice to low doses of estradiol and other estrogenic chemicals like BPA and offspring can lead to androgen sensitivity and consequently to an increased expression of AR in the prostate in pubertal and young adults rodents (Nagel et al, 1997;Gupta, 2000;Brandt et al, 2014). Furthermore, in a previous study we observed that estrogen supplementation even in a lowandrogen environment (after castration) increased AR expression in Mongolian gerbil ventral prostate through paracrine signaling mechanisms involving ER-a (Scarano et al, 2009). Maternal dietary GEN tended to normalize AR expression in the VL in male offspring from dams exposure to low-dose BPA.…”
Section: Discussionmentioning
confidence: 78%
“…Previous reports have shown that exposure to estradiol may increase the synthesis of collagen in the stromal cells and make collagen bundles thicker in rodent prostate (Tilley et al, 1989;Prins et al, 2007;Scarano et al, 2005Scarano et al, , 2008. However, serum levels of estradiol on PND21 did not differ among the experimental group but some toxicological studies in which EDs were administered during pregnancy showed that hormone levels tend to normalize after exposure; however, the tissue-specific effects remain (Putz et al, 2001;Scarano et al, 2009). A significant reduction in the cell proliferation index related to the partial recovery of prostatic architecture in the VP was observed on PND21.…”
Section: Discussionmentioning
confidence: 90%
“…Although there is insufficient data for DBP effects on human reproduction, some studies in rodents have reported the influence of DBP on the male reproductive system [Alam et al 2010;Scarano et al 2009;Hoshi and Ohtsuka 2009]. To date, however, the mechanisms of reproductive toxicology of DBP are still unclear and need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are growing concerns regarding the toxicity of DBP exposure on male reproduction (Alam et al, 2010;Scarano et al, 2009). Reported reproductive effects of DBP include alteration in activities of steroidogenic enzymes, alteration in testosterone metabolism and decreased levels of plasma testosterone; they are suspected of acting as endocrine distuptors that have the potential to modify normal endocrine function (Hirosawa et al, 2006;Xiaofeng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%